PERAN MEDIA DIGITAL SEBAGAI SALURAN KOMUNIKASI KEAGAMAAN DI ERA KONVERGENSI MEDIA - Abdurahman, Maman; Faruq, Umar (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
The transformation of information and communication technology has encouraged religious organizations to adapt their da'wah message dissemination strategies through digital platforms. Muhammadiyah, as one of the largest Islamic organizations in Indonesia, has developed a digital media ecosystem known as the Muhammadiyah Digital Center (MDC) in response to the changing communication landscape in the era of media convergence. This study aims to analyze the role of digital media as a channel of religious communication within the MDC ecosystem, identify patterns of digital da'wah content management, and describe the communication strategies applied to reach Muslim audiences in digital spaces. A qualitative method with a case study approach was used, with data collected through in-depth interviews with MDC managers, participatory observation of digital platform activities, and document analysis of organizational communication policies. The results show that MDC has built a structured and integrated digital communication infrastructure, including official websites, social media channels, podcasts, and live streaming services. The content management pattern is centralized yet adaptive to the characteristics of each platform. The communication strategies applied emphasize moderation, inclusivity, and responsiveness to contemporary issues. Media convergence has proven to significantly expand the reach of Muhammadiyah's religious communication while also presenting new challenges related to digital literacy and content management amid the rapid flow of digital information